Derivation and validation of a novel Emergency Surgery Acuity Score (ESAS). Issue 2 (August 2016) - Sangji, Naveen F.; Bohnen, Jordan D.; Ramly, Elie P.; Yeh, Daniel D.; King, David R.; DeMoya, Marc; Butler, Kathryn; Fagenholz, Peter J.; Velmahos, George C.; Chang, David C.; Kaafarani, Haytham M.A.
Abstract : BACKGROUND: There currently exists no preoperative risk stratification system for emergency surgery (ES). We sought to develop an Emergency Surgery Acuity Score (ESAS) that helps predict perioperative mortality in ES patients. METHODS: Using the 2011 American College of Surgeons' National Surgical Quality Improvement Program (ACS-NSQIP) database (derivation cohort), we identified all surgical procedures that were classified as "emergent." A three-step methodology was then performed. First, multiple logistic regression models were created to identify independent predictors (e.g., patient demographics, comorbidities, and preoperative laboratory variables) of 30-day mortality in ES. Second, based on the relative impact of each identified predictor (i.e., odds ratio), using weighted averages, a novel score was derived. Third, using the 2012 ACS-NSQIP database (validation cohort), the score was validated by calculating its C statistic and evaluating its ability to predict 30-day mortality. RESULTS: From 280, 801 NSQIP cases, 18, 439 ES cases were analyzed, of which 1, 598 (8.7%) resulted in death at 30 days. The multiple logistic regression analyses identified 22 independent predictors of mortality. Based on the relative impact of these predictors, ESAS was derived with a total score range of 0 to 29. ESAS had a C statistic of 0.86; the probability of death at 30 days gradually increased from 0% to 36% then 100% at scores of 0, 11, and 22, respectively. In the validation phase, 19, 552 patients were included, the mortality rate was 7.2%, and the ESAS C statistic stayed at 0.86. CONCLUSION: We have therefore developed and validated a novel score, ESAS, that accurately predicts mortality in ES patients. Such a score could prove useful for (1) preoperative patient counseling, (2) identification of patients needing close postoperative monitoring, and (3) risk adjustment in any efforts at benchmarking the quality of ES. LEVEL OF EVIDENCE: Prognostic/epidemiologic study, level III.